2019
DOI: 10.1016/j.ecoenv.2018.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potentially toxic trace element contamination in urban allotment soils and their uptake by onions: A preliminary case study from Sheffield, England

Abstract: Toxic trace element (TTE) contamination in urban soils may pose potential health risks, especially in cities with previous industrial activities. This study aimed to investigate soil contamination in urban allotments in Sheffield, the uptake of TTEs in autumn and spring sown onions (Allium cepa), and their potential risks on human health via consumption of the crops. Paired soil and plant samples were taken in triplicates from four private allotments to assess potentially elevated levels of lead (Pb), zinc (Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
(91 reference statements)
0
17
1
Order By: Relevance
“…113 The use of brownfields for gardening and wastewater for irrigation can pose serious problems related to contamination of the vegetables produced in these areas. 114,115 Some urban areas studies have shown the levels of pollutant accumulation in vegetables did not threaten human health, such as Barcelona, Spain 113,116 ; Sevilla, Spain 117 ; Lisbon, Portugal 118 ; Madrid, Spain 119 ; Sheffield, UK 120 ; and Braganca, Portugal. 121 However, in other cities, the pollutant levels identified were high and threatened human health, including Rio de Janeiro, Brazil 122 ; Daejeon, South Korea 123 ; Rome, Italy 124 ; Melbourne, Australia 125 ; Dera Ismail Khan, Pakistan 126 ; and Ghaziabad, India.…”
Section: Soil Pollution and Human Healthmentioning
confidence: 99%
“…113 The use of brownfields for gardening and wastewater for irrigation can pose serious problems related to contamination of the vegetables produced in these areas. 114,115 Some urban areas studies have shown the levels of pollutant accumulation in vegetables did not threaten human health, such as Barcelona, Spain 113,116 ; Sevilla, Spain 117 ; Lisbon, Portugal 118 ; Madrid, Spain 119 ; Sheffield, UK 120 ; and Braganca, Portugal. 121 However, in other cities, the pollutant levels identified were high and threatened human health, including Rio de Janeiro, Brazil 122 ; Daejeon, South Korea 123 ; Rome, Italy 124 ; Melbourne, Australia 125 ; Dera Ismail Khan, Pakistan 126 ; and Ghaziabad, India.…”
Section: Soil Pollution and Human Healthmentioning
confidence: 99%
“…Lack of a sufficient amount of clean water for irrigation leads to the used of wastewater in many developing cities (Sayo et al, 2020). Vegetable gardens located in urban and peri-urban areas are at risk of been contaminated with dangerous HM from various sources (Bi et al, 2018;Hong et al, 2019) due to intense industrial activities that are taking place in many cities (Deng et al, 2020;Weber et al, 2019) which releases tonnes of contaminants (Margenat et al, 2018). Atmospheric deposits through fossil fuel combustion and dust from contaminated areas intensify soil contamination in urban areas (Weber et al, 2019).…”
Section: The Roles Of Urban Agriculture In Food Crops Hm-contaminationmentioning
confidence: 99%
“…Vegetable gardens located in urban and peri-urban areas are at risk of been contaminated with dangerous HM from various sources (Bi et al, 2018;Hong et al, 2019) due to intense industrial activities that are taking place in many cities (Deng et al, 2020;Weber et al, 2019) which releases tonnes of contaminants (Margenat et al, 2018). Atmospheric deposits through fossil fuel combustion and dust from contaminated areas intensify soil contamination in urban areas (Weber et al, 2019). A systemic review conducted by Frank et al (2019) in United states showed that the Pb content of the soil in the urban areas is three times higher than in the soil outside cities.…”
Section: The Roles Of Urban Agriculture In Food Crops Hm-contaminationmentioning
confidence: 99%
“…Food safety is a key issue in the production of home-grown vegetables in cities [5][6][7][8][9][10]. The question arises as to whether urban soil is a good substrate to produce vegetables for home consumption due to the risk of its contamination with metals [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Food safety is a key issue in the production of home-grown vegetables in cities [5][6][7][8][9][10]. The question arises as to whether urban soil is a good substrate to produce vegetables for home consumption due to the risk of its contamination with metals [6,[10][11][12]. Vegetables grown on urban soils with a high concentration of heavy metals (especially toxic ones) may accumulate these toxins in edible parts, and when consumed, they are incorporated into the food chain.…”
Section: Introductionmentioning
confidence: 99%